Burden of community-acquired pneumonia in adults over 18y of age - Kosar, Filiz; Alici, Devrim Emel; Hacibedel, Basak; Yigitbas, Burcu Arpinar; Golabi, Pejman; Cuhadaroglu, Caglar (TAYLOR \& FRANCIS INC, 2017)
This study aimed to determine the economic burden and affecting factors in adult community-acquired pneumonia (CAP) patients (>= 18years) by retrospectively evaluating the data of 2 centers in Istanbul province, Turkey. Data of outpatients and inpatients with CAP from January 2013 through June 2014 were evaluated. The numbers of laboratory analyses, imaging, hospitalization days, and specialist visits were multiplied by the relevant unit costs and the costs of the relevant items per patient were obtained. Total medication costs were calculated according to the duration of use and dosage. The mean age was 61.56 +/- 17.87y for the inpatients (n = 211

48.6\% female) and 53.78 +/- 17.46y for the outpatients (n = 208

46.4\% male). The total mean cost was Euro556.09 +/- 1,004.77 for the inpatients and Euro51.16 +/- 40.92 for the outpatients. In the inpatients, laboratory, medication, and hospitalization costs and total cost were significantly higher in those >= 65y than in those < 65 y. Besides the hospitalization duration, specialist visit, imaging, laboratory, medication, and hospitalization costs and total cost were significantly higher in those hospitalized more than once than in those hospitalized once. While the specialist visit cost was higher in the inpatients with comorbidities, the imaging cost was higher in the outpatients with comorbidities. CAP poses a higher cost in inpatients, elders, and individuals with comorbidities. Costs can be decreased by rational decisions about hospitalization and antibiotic use according to the recommendations of guidelines and authorities. Vaccination may decrease medical burden and contribute to economy by preventing the disease, especially in risk groups.
Keywords: adults; burden; Community-acquired pneumonia; cost; vaccination